Impacts of different culture times on pregnancy outcomes after thawing of cleavage stage embryos - Jieyou Wang; Linna Ma; Jiaoqi Mei; Linjiang Li; Wen Xu; Weimin Jiang; Yueyan Wei; Yu Xu; Shaoqing Sun; Yanlin Ma; Qi Li (BMC, 2023)
Abstract Objective This study assessed the impacts of in vitro culture times of cleavage embryos on clinical pregnancy outcomes. Methods This retrospective cohort study was performed at the Reproductive Medicine Department of Hainan Modern Women and Children's Hospital in China between January 2018 and December 2022. Patients who first underwent frozen embryo transfer with in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) cycles on day 3 were included. According to the time of embryo culture after thawing, the embryos were divided into long-term culture group(18-20 h) and short-term culture group (2-4 h). The clinical pregnancy rate was regarded as he primary outcome. To minimize confounding factors and reduce selection bias, the propensity score matching was used to balance the effects of known confounding factors and to reduce selection bias. Stratified analyses and multiple logistic regression analyses were used to evaluate the risk factors affecting the clinical pregnancy outcomes after matching. Results General characteristics between two groups were comparable after matching. In the long-term culture group, 266/381 (69.81%) embryos had more than 10 blastomeres, and 75/381 (19.68%) reached the morula stage. After overnight culture, the implantation rate (27.97% vs. 14.28%, P = 0.018) and clinical pregnancy rate (38.46% vs. 22.5%, P = 0.05) were increased in the group with proliferating blastomeres. The long-term culture group trended to have a higher clinical pregnancy rate compared with the short-term culture group (35.74% vs. 29.79%). No statistical differences in clinical pregnancy outcomes between the two groups were observed after matching, including the rates of implantation (25.46% vs23.98%), miscarriages (25% vs. 22.85%), ongoing pregnancy rate (76.2% vs. 77.15%) and live birth rate (26.8% vs. 22.98%). Stratified analyses were performed according to the age of the patients. After matching, there were no significant differences in the clinical pregnancy, implantation and miscarriage rates between the two groups for patients > 35 or ≤ 35 years of age. Subgroup analyses were performed according to the quality of the transferred embryos. There were no significant differences in the clinical outcomes, between two groups after embryos transferred with the same quality. Multivariate Logistic regression analysis was used to evaluate the influencing factors of clinical pregnancy outcomes after matching. Culture time was not found to be an independent predictor for clinical pregnancy [OR 0.742, 95%CI 0.487 ~ 1.13; P = 0.165]. The age of oocyte retrieval [OR 0.906, 95%CI 0.865 ~ 0.949; P <0.001] and the number of high-quality embryos transferred [OR 1.787, 95%CI 1.256 ~ 2.543; P = 0.001] were independent factors affecting clinical pregnancy outcomes. Conclusions In vitro 18-20 h culture of embryos with either good-or non-good-quality will not adversely affect the clinical pregnancy.